2022
DOI: 10.1145/3472810
|View full text |Cite
|
Sign up to set email alerts
|

Age-Invariant Face Recognition by Multi-Feature Fusionand Decomposition with Self-attention

Abstract: Different from general face recognition, age-invariant face recognition (AIFR) aims at matching faces with a big age gap. Previous discriminative methods usually focus on decomposing facial feature into age-related and age-invariant components, which suffer from the loss of facial identity information. In this article, we propose a novel Multi-feature Fusion and Decomposition (MFD) framework for age-invariant face recognition, which learns more discriminative and robust features and reduces the intra-class var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…We found that the levels of the 13 ROIs in a hand X-ray image are correlated to each other, the Pearson correlation coefficients of the 13 ROIs are calculated and shown in Table 1. To further benefit from the correlation coefficients, we implement a simple and effective self-attention mechanism [41,42] within the Densenet. As in Fig.…”
Section: Self-attention Transfer Network For Baamentioning
confidence: 99%
“…We found that the levels of the 13 ROIs in a hand X-ray image are correlated to each other, the Pearson correlation coefficients of the 13 ROIs are calculated and shown in Table 1. To further benefit from the correlation coefficients, we implement a simple and effective self-attention mechanism [41,42] within the Densenet. As in Fig.…”
Section: Self-attention Transfer Network For Baamentioning
confidence: 99%
“…In ResNet(2+1)D [16], new convolution kernels were explored and the C3D model was optimized in terms of parameters and running speed. Video-based 3D multi-scale detection [17,18] [19][20][21] are particularly important for streaming data processing in the machine-learning field, for example, task-adaptive attention method [22] used in image captioning and self-attention and multi-feature fusion method [23] used in face recognition. Inspired by human vision, the Institute for Human-Machine Communication from Munich University Germany proposed a fast and real-time video action detection method (You Only Watch Once, YOWO) [24], which achieves the highest efficiency at present.…”
Section: Related Workmentioning
confidence: 99%
“…With the boosted development of artificial intelligence in the recent decade, we also witnessed research works [28] , [29] , [30] , [31] , [32] integrating machine learning approaches into multimedia like image retrieval and face recognition. For example, Yan et al [28] introduced a multi-view deep neural network into the hash learning domain to significantly improve the performance in image retrieval.…”
Section: Related Workmentioning
confidence: 99%